The Models of Nagari Indigenous Governments in West Sumatra (Jurnal Bina Praja, 2020)
Law No. 6 of 2014 concerning Villages provides opportunities for indigenous communities to form indigenous village governments. Nagaris have an established government system, and yet it is getting blurry and dysfunctional institutionally as rules and regulations concerning village governments change. This study aims to explore and rediscover the nagari government models according to the Minangkabau customs. Data were collected with a mixed-method approach, including survey, observation, interview, and focus group discussion (FGD) methods. This study found that, first, there are two nagari government models in the Minangkabau customs, namely the aristocratic model and the democratic model. Second, the cultural identity of the Minangkabau society is reflected in the concept of banagari, as the traditional system and the government system as an autonomous and independent entity. Third, the nagari government system accommodates two systems that are running simultaneously, namely the state government system and the indigenous government system, in the context of banagari life by using a system that divides the government into three branches, namely an executive, a legislature, and a judiciary.
Keywords: Nagari; Models of Indigenous Governments; Democracy; Sovereignty